Essential criteria for quality OPD services as perceived by patients in a tertiary care hospital in Faridabad City - Goyal, Pooja; Kumar, Deepak; Dixit, Shivam; Srivastav, Suyesh; Singh, Abhishek (International Journal of Research in Medical Sciences, 2016)
Background: In a health care system, patient’s perception about quality is of utmost importance to understand the relationship between quality of care and utilization of health services. It is also treated as an outcome of health care delivery. The current study was planned to improve the quality of services rendered at tertiary care facilities by utilizing the clients’ perception regarding the services. Methods: The present study was a hospital based, cross sectional type of descriptive study. Data collection was done through exit interviews among randomly selected new OPD attendees in a tertiary care hospital using a pre- structured, pretested Performa as the study tool. Likert’s scale was used for assessment of client perception on quality of health services and overall satisfaction. Data was analyzed using SPSS 17.0. Results: Present study was comprised of 402 subjects including 216 males and 184 females. It was observed that 93.9% subjects perceive quality of services as good and 87.8% clients were satisfied with the services rendered at the hospital. Good doctor behavior (51.7%), medicine availability (38.6%) and cleanliness (35.4%) in the hospital were found to be most important reasons behind the satisfaction of the clients as verbally expressed by them. Among dissatisfied (12.2%) study subjects, poor medicine availability (57.1%) and poor investigation facilities were considered (48.9%) as major reasons behind their dissatisfaction. Conclusions: Majority of our patients were satisfied after availing health services at our hospital. We have identified a few deficient areas in terms of service delivery and the same will be bridged as early as possible in order to achieve universal patient satisfaction.